1982
DOI: 10.1002/1098-2337(1982)8:3<261::aid-ab2480080304>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior induced by electrical stimulation in the midbrain central gray of male rats

Abstract: Electrical stimulation via electrodes implanted in the lateral hypothalamus may induce intraspecific aggressive behavior. Small electrolytic lesions placed via these electrodes resulted in a five– to tenfold increase in the current threshold for aggression. Degenerating fibers were stained by means of the Fink‐Heimer method and could be followed caudally to the dorsal midbrain central gray and to the mammillary bodies. A few axons could be traced rostrally to the medial septum. Aggression could be induced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Electrical stimulation of the PAG induces defensive rage in cats, and attack in the rat (Mos et al ., 1982). Although attack cannot be elicited easily from this area in the rat, its involvement in mediating aggression has been established (Bandler et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation of the PAG induces defensive rage in cats, and attack in the rat (Mos et al ., 1982). Although attack cannot be elicited easily from this area in the rat, its involvement in mediating aggression has been established (Bandler et al ., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In lactating female rats the PAG appears to modulate nursing as well as aggression (Lonstein and Stern, 1997). Similarly, PAG stimulation elicits aggressive behavior in rats and cats (Mos et al, 1982;Bandler and Carrive, 1988). The PAG also plays a role in receptivity, as lesions lead to deficits in lordosis (Floody and O'Donohue, 1980).…”
Section: Periaqueductal Gray/central Gray (Pag/cg) Mammalsmentioning
confidence: 99%
“…Limited electrophysiological recordings revealed that cells related to fighting exist in the PAG [106]. Electric stimulation of the PAG could elicit attack though it was often accompanied by motor disturbance [107]. Electric lesion in the PAG decreased natural aggression and increased the current threshold required to induce attack from the hypothalamus [108].…”
Section: The Motor Output Of Social Behaviors Beyond the Hypothalamusmentioning
confidence: 99%